A controlled study of Faradic disruption of obsessive ideation in the treatment of obsessive neurosis - Kenny, Frank Townsend (1974)
Thesis (M.Sc.)--Memorial University of Newfoundland, 1975. Psychology Bibliography: leaves 103-108.